Influence of acute physical exercise on cognitive and motor behavior in an experimental model of alzheimer’s disease - Furmann, Meiriélly (2019)
Introduction: Aging causes alterations in various executive and cognitive functions, mainly related to the incidence of dementia, especially Alzheimer’s disease (AD). Several studies mention physical exercise as a preventive resource for depressive symptoms. Objective: To investigate the cognitive and behavioral alterations related to AD that are capable of slowing disease progression and its complications. Methods: The sample consisted of 10 male Wistar rats, divided into 2 groups (n = 5), swimming and Alzheimer + swimming, with a 6-day intervention protocol. The elevated plus maze test was used to assess anxiety, the Morris water maze for spatial memory, the isolation box for aversive memory, and the open field test to assay motor behavior. Results: There was improvement in spatial memory in the Swimming group (169 ± 142.9 x 24.2 ± 31.3), but motor behavior deteriorated after exercise. An increase in anxious behavior (8 ± 13.03 x 67.8 ± 48.1) was observed in the animals with AD. This is a relevant characteristic of the disease, which did not improve after acute exercise. By analyzing the size effect, it was possible to observe a difference in the Alzheimer + swimming group in terms of reduced anxiety and improved motor behavior after exercise. Despite the benefits of physical exercise for AD symptoms, there is still no consensus on the type of physical exercise and length of intervention necessary to achieve a positive response as a treatment method, since studies are yet to confirm this fact in an acute or chronic manner. Conclusion: Acute physical exercise was not fully effective as a means of treating behavioral alterations related to AD, but had a mean effect on the size effect analysis of motor behavior and anxiety, specifically. Level of evidence IV; Investigation of treatment outcomes.